The expression \( 27x^3 - 64y^3 \) represents a difference of cubes, which can be factored using the formula:
\[ a^3 - b^3 = (a - b)(a^2 + ab + b^2) \]
In this case, we can identify \( a = 3x \) (since \( (3x)^3 = 27x^3 \)) and \( b = 4y \) (since \( (4y)^3 = 64y^3 \)). Applying the difference of cubes formula:
- \( a - b = 3x - 4y \)
- \( a^2 = (3x)^2 = 9x^2 \)
- \( ab = (3x)(4y) = 12xy \)
- \( b^2 = (4y)^2 = 16y^2 \)
Thus, the full factorization is:
\[ 27x^3 - 64y^3 = (3x - 4y)(9x^2 + 12xy + 16y^2) \]
The linear factor of the expression \( 27x^3 - 64y^3 \) is \( 3x - 4y \).
So the correct response from the options you provided is:
3x - 4y